Pembuatan Website Profil Bursa Kerja Khusus (Bkk) Sekolah Menengah Kejuruan Negeri Dua Karanganyar - Marsanto, Ali; Purnama, Bambang Eka (Seruni - Seminar Riset Unggulan Nasional Inoformatika dan Komputer, 2013)
Abstrac: Vocational High School Karanganyar Country 2 is one of the vocational school in Karanganyar district and has 4 major techniques of Machining Engineering, Textile Engineering,Software Engineering (RPL) and Technical Ototronik.Sebagai international vocational school Vocational School Negeri 2 Karanganyar must have the Special Jobs (BKK), which is the body which handles the distribution issue with graduates and job openings. But the delivery of information BKK Vocational High School Country 2 Karanganyar still sticking by the announcement on the bulletin board when there was BKK on a job vacancy or info and schedule testing of the company. This is a problem for an alumnus who distance away from the school house, and has been in the outer regions, it is necessary to need a website BKK Vocational High School Country 2 Karanganyar which can be accessed anywhere by an alumnus. The purpose of this research is to produce websites Vocational High School BKK Country 2 Karanganyar which can be accessed anywhere by an alumnus. Benefits sisitem this web-based information is easier to deliver information on the work schedule and nfo from the company's test. is information system using the programming language PHP with My SQL databases and display using Adobe Dreamweaver to make it more interesting. Making profile website system is useful for BKK Vocational High School in Country 2 Karanganyar delivery BKK information. Key word : BKK,Web Abstrak: Sekolah Menengah Kejuruan Negeri 2 Karanganyar adalah salah satu sekolah kejuruan yang berada di Kabupaten Karanganyar dan memiliki 4 jurusan teknik teknik yaitu Teknik Pemesinan, Teknik Tekstil, Rekayasa Perangkat Lunak (RPL) dan Teknik Ototronik.Sebagai sekolah kejuruan bertaraf internasional Sekolah Menengah Kejuruan Negeri 2 Karanganyar harus memiliki Bursa Kerja Khusus (BKK) ,yaitu badan yang menangani masalah penyaluran lulusan dan lowongan pekerjaan. Tetapi penyampaian informasi BKK Sekolah Menengah Kejuruan Negeri 2 Karanganyar masih dengan cara menempel pengumuman di papan pengumuman BKK pada saat ada info lowongan pekerjaan ataupun info dan jadwal tes dari perusahaan. Hal itu menjadi masalah bagi alumnus yang jarak rumah jauh dari sekolah, dan telah berada di luar daerah, maka perlu dibutuhkan suatu website BKK Sekolah Menengah Kejuruan Negeri 2 Karanganyar yang dapat diakses dimanapun oleh alumnus. Tujuan penelitian ini untuk menghasilkan website BKK Sekolah Menengah Kejuruan Negeri 2 Karanganyar yang dapat diakses dimanapun oleh alumnus. Manfaat sisitem informasi berbasis web ini adalah mempermudah penyampaian informasi pekerjaan jadwal dan info tes dari perusahaan . Pembuatan sistem informasi ini menggunakan bahasa pemrograman php dengan database My SQL dan tampilan menggunakan Adobe Dreamweaver agar lebih menarik. Pembuatan website profil BKK ini bermanfaat bagi BKK Sekolah Menengah Kejuruan Negeri 2 Karanganyar dalam penyampaian informasi BKK. Kata Kunci : Bursa Kerja Khusus (BKK), Web